Long‐term neurodevelopmental outcomes of the pump twin in twin reversed arterial perfusion sequence treated by radiofrequency ablation. (25th September 2021) - Ozawa, Katsusuke; Wada, Seiji; Muromoto, Jin; Sugibayashi, Rika; Wada, Yuka Sano; Ito, Yushi; Sago, Haruhiko
Abstract: Objectives: To assess long‐term neurodevelopmental outcomes in children after radiofrequency ablation (RFA) for twin reversed arterial perfusion (TRAP) sequence. Methods: This cross‐sectional study included children who underwent RFA for the TRAP sequence between 2012 and 2018. We assessed neurodevelopment in children using the Kinder Infant Development Scale, a validated questionnaire. The developmental quotient (DQ) assessed in nine subscales was calculated as the developmental age divided by the chronological age. Neurodevelopmental delay (NDD) was defined as a DQ of <70 points. Results: In total, 38 children from 37 pregnancies underwent RFA for the TRAP sequence during the study period; 6 fetuses died in utero. We sent the questionnaire to the parents of the 32 surviving children and obtained answers for 27 (84%). The median age at the assessment was 2 years and 5 months old. The median total DQ was 111 (80–150). Most median DQs in the nine subscales were above 70. The incidence of NDD was 0% (0/27). There were no marked differences in DQ by chorionicity. Conclusions: Children who survived after RFA for TRAP sequence showed favorable long‐term neurodevelopmental outcomes. Radiofrequency ablation seems to rarely affect fetal neurodevelopment. Pregnant women with TRAP sequence are encouraged to be treated by RFA. Key points: What's already known about this topic? Radiofrequency ablation (RFA), which induces the coagulation of tissue, is commonly used to treat twin reversed arterial perfusion (TRAP) sequence because of the minimal invasiveness of the technique. The survival rate of the pump twin of TRAP sequence treated by RFA is more than 80%; however, the long‐term neurodevelopmental outcomes of survivors have rarely been investigated. What does this study add? Pump twins of TRAP sequence who survived after RFA showed favorable long‐term neurodevelopmental outcomes with a median developmental quotient of more than 100. Radiofrequency ablation in fetal surgery itself seems to rarely affect fetal neurodevelopment.